Quantitative attribution of 2016 extreme arctic warmth: comparison between late winter and early spring - Junjie Zhu; Ke Fan; Shengping He; Tuantuan Zhang; Yi Deng; Song Yang; Deliang Chen; Kaiqiang Deng; Wei Yu; Baoqiang Tian; Hoffman H N Cheung (Environmental Research Letters)
A deep, large-scale warmth occurred in the Arctic from January to April 2016, but the roles of various physical processes in this period have not been quantified. Here, we utilize an updated version of the coupled atmosphere‒surface climate feedback response analysis method to quantitatively attribute the extreme warmth. Our results show distinct characteristics associated with the warm anomaly in January‒February and March‒April. This extreme Arctic warmth is largely explained by the positive contributions of atmospheric dynamics, which are dominated by horizontal advection in January‒February and by adiabatic heating and vertical terms in March‒April. Compared with January‒February, an increase in solar radiation leads to an enhanced positive contribution from surface albedo processes in March‒April. Water vapor processes provide considerable positive contribution during both periods. In contrast, surface dynamic processes provide positive contribution in January‒February but negative contribution in March‒April, while cloud processes provide nearly negative contribution during both periods, primarily through their longwave effects.